La discriminación de género en la relación laboral: igualdad formal, igualdad material y acción positiva (Tema Central) - Sierra Hernáiz, Elisa (2018)
One of biggest problems of female workers is to get real equality in their working conditions. Affirmative actions or preferential treatment can be a solution to overcome the effects of social discrimination at work. Nowdays the main obstacle to set up is not the legal delimitation in the European Law but the interpretation of cases law that limit its application in employment contracts. This situation represents a loss in the struggle for equal opportunity and rights for female works.